Characterization of Biodegradable Avocado Seed Starch Films Reinforced with Chitosan and Plasticized with Glycerol - Hartanti, Adelia; Nur Wahyudi, Mohamad; Fahmi Hakim, Muhammad; Rohmaful Aeni, Alfieta; Agustina Sari, Dessy (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2025)
Researchers have developed biodegradable bioplastics from renewably sourced natural materials in response to the environmental consequences of synthetic plastics. This study looks at how different amounts of glycerol and chitosan affect the properties of bioplastics made from avocado seed starch. This study evaluated the mechanical, hydrophilic, and degradation properties in terms of tensile strength, elongation at break, thickness, water absorption, and structural stability over time. The results showed that an increase in glycerol content improved flexibility and elongation but impaired tensile strength and water resistance. On the other hand, the increase of chitosan concentration contributes to a significant enhancement of tensile strength, water resistance, and stability. The mixture A3 (1 ml glycerol, 4.5 g chitosan) was thought to have good mechanical stiffness (16.560 ± 3.661 MPa) and water resistance. On the other hand, B1 (2 ml and 2.5 g) had better elasticity (elongation: 32.299 ± 8.910%). Upon performing degradation analysis, B-series samples exhibited a high hydrophilicity, which caused faster breakdown as opposed to A-series samples. Avocado seed starch plasticized by a combination of chitosan and glycerol shows promise as an environmentally friendly plastic, and this study shows a way toward fine-tuning both mechanical and hydrophilic properties to produce biodegradable bioplastics